Research data management in Turkey: perceptions and practices. Issue 2 (19th June 2017) - Aydinoglu, Arsev Umur; Dogan, Guleda; Taskin, Zehra
Abstract : Purpose: The massive increase in research data being produced nowadays has highlighted the importance of research data management (RDM) to science. Research data not only have to be cost effective but also reliable, discoverable, accessible, and reusable. In this regard, the purpose of this paper is to investigate the perceptions and practices of Turkish researchers on the subject of RDM. Design/methodology/approach: An online survey was distributed to the academicians in 25 universities in Turkey, and 532 responses were gathered. Findings: Results indicate that although Turkish researchers are aware of the benefits of data management, are willing to share their research data with certain groups, and have decent preservation habits, they express that they lack the technical skills and knowledge needed for RDM. In addition, no institutionalized support (staff, training, software, and hardware) is provided to researchers. Research limitations/implications: A well-structured data strategy or policy that includes resource allocation (awareness, training, software/hardware) and is supported by Turkish research agencies is required for better data management practices among researchers in Turkey. Originality/value: This is the first study that investigates the data practices of Turkish academics who produce around 30, 000 scientific articles annually that are indexed by Web of Science. It contributes to the growing literature on RDM.